Personalizing Breast Cancer Irradiation Using Biology: From Bench to the Accelerator - Azria, David; Brengues, Muriel; Gourgou, Sophie; Bourgier, Celine (Frontiers in Oncology, 2018)
While adjuvant treatments of early breast cancers (BCs) had significantly improved patients’ overall survival, some of them will still develop locoregional relapses and/or severe late radio-induced toxicities. Here, we propose to review how to personalize locoregional treatment by identifying patients at high and low risk of locoregional relapse, patients at risk of late radio-induced side effects. We will, therefore, discuss how to enhance BC radiosensitivity. Finally, we will address how personalized radiotherapy could be implemented in prospective clinical trials.